Hesperidin Attenuates Influenza a virus (H1N1) Induced Lung Injury in Rats through its Anti-Inflammatory Effect. Issue 7 (October 2018) - Ding, Zhen; Sun, Gengyun; Zhu, Zhongming
Background: Influenza A viruses (IAV) can cause pandemics and are big threats to human health. Inflammation is the main pathological process in the lungs after IAV infection. We aimed to investigate whether hesperidin, a well-known anti-inflammatory compound, could be effective in improving IAV-induced lung injury. Methods: We generated a rat model using H1N1 virus infection, and intraperitoneally injected different doses of hesperidin for 5 days. Pulmonary function was analysed. Local inflammatory state was profiled by immune cells and cytokines. Pulmonary microvascular endothelial cells were isolated from rats and used to test the effects of hesperidin in vitro . Results: Hesperidin showed efficacy in improving H1N1-induced impairment of pulmonary function in a dose-dependent manner. Local numbers of immune cells and concentrations of cytokines were significantly limited by hesperidin. However, we found that hesperidin neither inhibited virus replication, nor rescued infected pulmonary microvascular endothelial cells. Rather, we observed that hesperidin reduced pro-inflammatory cytokine production by suppressing mitogen-activated protein kinase (MAPK) signalling pathways. Conclusions: Hesperidin could alleviate H1N1-induced impairment of pulmonary function by inhibiting cytokine production in pulmonary microvascular endothelial cells through MAPK signalling pathways.